Optimal Operation Scheduling of a Pumping Station in East Route of South-to-north Water Diversion Project. (May 2017) - Zhuan, Xiangtao; Li, Wei; Yang, Fei
Abstract: The fourth Huaian pumping station is one of the second-stage pumping stations in the South-to-North water diversion project (east route) in China. The operation optimization problem of three pumps in the station is formulated to reduce the electricity cost with the flow demand satisfied. With the characteristics of the problem analyzed, an decomposition method is proposed to reduce the dimensionality of the optimization problem and thus the computation time. Simulation shows the feasibility of proposed method in the reductions of the energy cost. The case study shows that the cost efficiency comes from two aspects: demand shift from the time intervals with high electricity price to those with low electricity price, and the operation mode with high energy efficiency.